Karst Ecosystems of Middle Timan, Russia: Soils, Plant Communities, and Soil Oribatid Mites - Elena N. Melekhina; Vladimir A. Kanev; Svetlana V. Deneva (Diversity, 2022)
Oribatid mites are distinguished by high taxonomic diversity and abundance in almost all natural zones; they are used as an indicator group of microarthropods in the study of natural landscapes and anthropogenically disturbed ecosystems. In the karst landscapes of the North, the oribatid mites are very poorly studied. The aim of this study was to investigate the diversity of soil types, plant communities, and oribatid mites in karst relief forms in the conditions of the northern taiga forests. The material was collected in July 2020 in the karst landscapes of Timan Ridge, found in the European northeast of Russia. The research sites were located in the profile of the karst crater and in the profile of the slope in the Ukhta River Valley. A sedge wetland community, and pine–bilberry–green-moss forest, located in the depression between glacial hills and uplands were also examined. A total of seven sites were examined. Geobotanical descriptions were made by standard methods, descriptions of the soil profile, and samples of the soil microfauna; 12 in each site were collected. A total of 51 oribatid mite species from 39 genera and 31 families were found. The highest taxonomic diversity of oribatids was noted in forest phytocenoses located in the upper part of the karst crater slope, the lower part of the karst crater slope, and on rock outcrops in the lower part of the slope in Ukhta river valley. Ordination of the oribatid mite community by NMDS method showed the association of sites S3, S4, and S5 located on the slope of the karst crater in one group, and sites S6 and S7 located on a slope in the Ukhta River Valley, as well as S2 (pine–bilberry–green-moss forest located in the depression between glacial hills and uplands), in another group. The swamp community was located separately from other communities. Species of oribatid mites, which created the specifics of each community, were noted. The specifics of the population of oribatid mites of karst landscapes were that along with the features of fauna, characteristic for zonal north-taiga forests (the predominance of polyzonal widespread species) were found the “conditionally southern” species, the main area of distribution of which is located in lower latitudes. The study provides the basis for future studies of poorly known oribatid mites of karst landscapes of Northern Europe.